2017
DOI: 10.1007/s12144-017-9657-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Parenting Stress During Early Adoptive Parenthood

Abstract: Parenting stress has a crucial influence on the parent-child relationship, the functioning of the family, and the development of children. Few studies have examined parenting stress in adoptive families during early parenthood, and fewer still have considered this issue in association with the quality of both couple and social relationships. The current study was intended to investigate predictors of parenting stress in a community sample of 56 adoptive parents from Italy, for a total of 112 participants. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 45 publications
4
23
1
1
Order By: Relevance
“…Results showed that prospective adoptive couples reported high levels of positive dyadic coping and low levels of negative dyadic coping, suggesting partners’ ability to successfully cope together with a common stressor, a high level of relationship satisfaction, and an average level of couple generativity. In line with the literature (Lansford et al, 2001; Ceballo et al, 2004; Rosnati et al, 2013; Canzi et al, 2017b), adoptive couples resulted to be well-equipped and to have relational resources, especially in terms of couple relationship functioning. It could be that couples choosing adoption are those who can count on a wide range of resources.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Results showed that prospective adoptive couples reported high levels of positive dyadic coping and low levels of negative dyadic coping, suggesting partners’ ability to successfully cope together with a common stressor, a high level of relationship satisfaction, and an average level of couple generativity. In line with the literature (Lansford et al, 2001; Ceballo et al, 2004; Rosnati et al, 2013; Canzi et al, 2017b), adoptive couples resulted to be well-equipped and to have relational resources, especially in terms of couple relationship functioning. It could be that couples choosing adoption are those who can count on a wide range of resources.…”
Section: Discussionsupporting
confidence: 66%
“…Much less investigated were their relational and marital resources (e.g., Levy-Shiff et al, 1990). Although research conducted on adoptive parents during later stages of the adoption transition evidenced a global positive quality of adoptive couples’ relationship (Lansford et al, 2001; Ceballo et al, 2004; Rosnati et al, 2013; Canzi et al, 2017b), we do not know much about prospective adoptive couples’ relationship more generally and about their coping ability more specifically. Nonetheless, a study examining adoptive couples relationship quality across the transition to adoption shows that pre-adoptive coping resources represent a protective factor against a pre to post-adoption decrease in satisfaction (Goldberg et al, 2010).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Fourth, in addition to providing adoptive parents with skills to better their parenting abilities directly, caregivers may benefit from supports to reduce the stress they experience during the transition. Previous research demonstrates that some adoptive parents may experience increased parenting stress (Canzi et al, 2019). Moreover, increased parenting stress in internationally adopting parents is associated with their own rates of depressive symptoms and perceptions of children's behavioral difficulties (Judge, 2004; Viana & Welsh, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, a child's entry into the family also results in the reorganization of the family system and new roles for both first-time parents and at the entrance of additional children (Lewis, Owen, & Cox, 1988; Volling, 2012). While adoptive parents do not on average experience greater parenting stress than biological parents, there are individual differences in parenting stress such that greater perceived child behavioral difficulties and longer durations of institutionalization are predictive of increased parenting stress during the initial transition for internationally adopting parents (Canzi, Ranieri, Barni, & Rosnati, 2019). Parenting stress can impede parents' abilities to be effective caregivers to children that in turn contribute to poorer child outcomes (Deater-Deckard, 1998).…”
Section: Early Life Adversity and Children's Regulatory Abilitiesmentioning
confidence: 99%